Ecophysiology and Ecology of Grassland - Xu, Bingcheng; Wen, Zhongming (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, "Ecophysiology and Ecology of Grassland", contains 11 research articles and 1 review that focus on recent advancements in integrated research on natural grasslands and artificial grasslands in response to human disturbances, abiotic stresses and climate change from a species to ecosystem level.